Taxpayer Compliance Factors of Swallow Birds Business in Indonesia - Wahyuni Rahmah; Riez Kifli Kolewora (Business Finence Analyst Co.,, 2024)
The swallow's nest industry plays an important role in the Indonesian economy as one of the leading export commodities with high demand in the international market. However, the level of tax compliance in this sector is still relatively low due to various obstacles, including lack of understanding of regulations, minimal socialization, and weak supervision. Previous studies have not comprehensively discussed the factors that influence tax compliance in the swallow's nest business, so further studies are needed to identify the main determinants and strategies for increasing taxpayer compliance. This study uses a qualitative descriptive method with a case study approach, where data is collected through in-depth interviews with swallow's nest business actors, tax authorities, academics, and swallow breeder associations. The results of the study indicate that tax compliance factors in this sector are influenced by understanding of regulations, clarity of tax policies, effectiveness of supervision, and the existence of tax incentives for compliant taxpayers. The implications of this study are the need for a more inclusive policy strategy, such as increasing socialization, harmonization of tax regulations, and provision of fiscal incentives to increase taxpayer compliance in the swallow's nest business.